Real‐Time Simulation of Nonequilibrium Nanocrystal Transformations. Issue 1 (31st October 2018) - Li, Xiao‐Yan; Zhu, Beien; Qi, Rui; Gao, Yi
Abstract: Nanoscience relies on a vast variety of metastable nanostructures with specific properties in different applications. Whether these metastable structures retain their unique structures after long‐time operation in real working conditions is a key question for evaluating their practical value. Here, the stability of a metastable nanostructure is shown, for example, the metallic hollow nanocrystals (hNCs), can be measured at macroscopic time scales (up to days) by a combined approach of density functional theory, all‐atom kinetic Monte Carlo method, and a well‐fitted nearest neighbor bonds model. The real‐time simulation results give detailed information on the structural evolution of Pt nanocrystals at different temperatures, which reproduces the experimental observations well. Further studies reveal that the intrinsic instability of hNCs comes from the fact that the outer‐surface refacetts faster than the inner‐surface due to the coordination‐number imbalance between them. Eliminating the driving force can efficiently stabilize the metastable nanostructures. Based on the above understanding, a general strategy is proposed for the rational design of highly stable metallic hNCs. This work not only provides insightful information and useful guidance for a wide variety of applications of hollow nanocatalysts but also paves the way for real‐time simulations of complex nonequilibrium nanocrystal transformations in real conditions. Abstract : Measuring the stabilities of metastable nanocrystals is a big challenge . Here, a real‐time all‐atom simulation of structural evolution of hollow metal nanocrystals (Pt, Pd, and Au) is performed at macroscopic timescales. The atomic mechanism of the instability is unveiled, and a general strategy to improve the stability is proposed.